PERANAN PENGAWASAN PARTISsIPATIF PEMILU 2024 DI BAWASLU KABUPATEN LOMBOK BARAT - Adriantini, Denda Nova (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
West Lombok Regency Bawaslu is increasing community participatory supervision of the implementation of the 2024 elections to realize democratic, transparent and accountable elections. For this reason, Bawaslu carries out various participatory supervision outreach activities to people from various backgrounds. These outreach activities include outreach to sub-district supervisory supervisors, ethnic and religious groups, people with disabilities, students, as well as creating election educational content on social media. The aim of these activities is to increase public understanding of the importance of actively participating in monitoring the election process in order to ensure maximum election implementation and prevent violations. With participatory supervision from various elements of society, it is hoped that it can help realize the quality implementation of the 2024 Election in West Lombok Regency.